2022
DOI: 10.3390/su14031910
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Risk-Assessment Method for Prefabricated Buildings Using EPC: A Case Study from China

Abstract: The prefabricated building has been proven to be an effective approach for enhancing the sustainability of the construction industry. In recent years, the Chinese government has promulgated a series of policy documents to promote the advancement of prefabricated buildings. However, in practice, there are still numerous problems related to design, production, and construction, as well as the coordination between various stages. This study aimed to fill the gap in research regarding the application of EPC (Engin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 66 publications
(137 reference statements)
0
8
0
Order By: Relevance
“…There are many shortcomings in current risk assessment methods for hoisting construction, mainly including the following reasons: (1) Complexity and uniqueness of hoisting construction: Hoisting construction involves complex operations, different site conditions, different equipment, and dynamic interactions between different elements. Many risk assessment methodologies fail to adequately capture the complexity and uniqueness of hoisting, resulting in a limited understanding of the associated risks [55,111,112].…”
Section: Risk Assessment Methodsmentioning
confidence: 99%
“…There are many shortcomings in current risk assessment methods for hoisting construction, mainly including the following reasons: (1) Complexity and uniqueness of hoisting construction: Hoisting construction involves complex operations, different site conditions, different equipment, and dynamic interactions between different elements. Many risk assessment methodologies fail to adequately capture the complexity and uniqueness of hoisting, resulting in a limited understanding of the associated risks [55,111,112].…”
Section: Risk Assessment Methodsmentioning
confidence: 99%
“…In the 1980s, China began to promote industrialized buildings, and PBPs gradually developed [5]. However, by the 1990s, the development of PBPs remained stagnant due to the constraints of the technical level, economic conditions, and people's cognition [26]. Although China introduced PBPs decades ago, the application of PBPs still faces major problems [31].…”
Section: Literature Review 21 Development Of Pbps In Chinamentioning
confidence: 99%
“…Rose [27] used an interactive research approach to conduct a case study of a Swedish PBP and proposed solutions for three major risks. Xia et al [26] analyzed the risks faced by PBPs using EPC from the perspective of general contractors, conducted an empirical study in Nanjing, China, and found that construction and design are the main factors that determine the level of project risk.…”
Section: Risk Management Of Pbpsmentioning
confidence: 99%
See 1 more Smart Citation
“…Xia et al proposed a coordination model for assembled buildings to address the design, production, and construction problems of assembled buildings. An evaluation system was developed to assess the construction progress and risks of assembled buildings (Xia et al 2022).…”
Section: Related Workmentioning
confidence: 99%